PENERAPAN STRATEGI DELAY FEEDBACK MENGGUNAKAN VIDEO TUTORIAL UNTUK MEREMEDIASI MISKONSEPSI SISWA PADA MATERI GERAK PARABOLA DI SMA NEGERI 1 SEPONTI - Sutrisno, Adi; Tandililing, Edy; Mahmuda, Diah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis pre-experimental study aims to investigate the implementation of the delay feedback strategy using video tutorials to remediate students' misconceptions of parabolic motion material in Seponti 1 High School. The sample of this study was the students of 11th grade Science 1 who were selected using the intact group technique based on the class with the lowest learning outcomes (pre-test). A diagnostic test consisting of 20 multiple choice questions with open reasoning is used as a research instrument to determine students' conceptions. Based on the results, the highest number of students' misconceptions at pre-test (95.23%) and post-test (38.09%) is on the concept of analyzing the time (t) of free fall simultaneously with different trajectories. The average decrease in the number of students' misconceptions per concept was 41.36%. Students' conceptions changed significantly (; ; ) after being given remediation learning. The price of the proportion that the students obtained was 0.516 (classified as medium). Delay feedback strategies using video tutorials are expected to be used as an alternative to remediation activities to improve students' misconceptions. Keywords: Delay Feedback Strategies, Misconceptions, Parabolic Motion, Remediation, Video Tutorials